2021
DOI: 10.3390/cosmetics8030075
|View full text |Cite
|
Sign up to set email alerts
|

Global Trends in Cosmetics Use-Related Adverse Effects: A Bibliometric Analysis of Literature Published during 1957–2021

Abstract: Cosmetic and beauty products, though not essential for physical health, go a long way in providing mental well-being and confidence, and hence are used substantially. Increasing utilization of varying cosmetic products leads to a multitude of adverse effects. There is more awareness about cosmeceutics, cosmetic products and their adverse effects, and studies on the same are currently trending. Bibliometrics has become a prominent and growing field of research in recent years. The aim of this research was to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…A finding to note is that though kajal was one of the most commonly used products by our study participants, it's the least common product to cause adverse reactions, consistent with other studies [6]. In our survey, the most common adverse reaction was itching followed by acne, identical to other studies [22]. Based on a study by Shiraz, Shakya et al, acne was the most disadvantageous adverse effect followed by rash [6,12].…”
Section: Girish Et Alsupporting
confidence: 89%
See 2 more Smart Citations
“…A finding to note is that though kajal was one of the most commonly used products by our study participants, it's the least common product to cause adverse reactions, consistent with other studies [6]. In our survey, the most common adverse reaction was itching followed by acne, identical to other studies [22]. Based on a study by Shiraz, Shakya et al, acne was the most disadvantageous adverse effect followed by rash [6,12].…”
Section: Girish Et Alsupporting
confidence: 89%
“…Based on a study by Shiraz, Shakya et al, acne was the most disadvantageous adverse effect followed by rash [6,12]. Al-Ghamdi et al found irritant contact dermatitis to be the most common adverse effect followed by acne, analogous to a bibliometric analysis [15,22].…”
Section: Girish Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…These products have a significant impact on the skin and can be beneficial, ineffective, or harmful. Women are more affected than men because they tend to use more cosmetics, in amount as well as in frequency 2–4 . Women may also experiment with different types of products.…”
Section: Introductionmentioning
confidence: 99%
“…Women are more affected than men because they tend to use more cosmetics, in amount as well as in frequency. [2][3][4] Women may also experiment with different types of products. Moreover, their skin is thinner as compared to men's.…”
mentioning
confidence: 99%